ANALISIS MEKANISME PENYELESAIAN PEMBIAYAAN BERMASALAH MELALUI LELANG BARANG JAMINAN DALAM UPAYA MENGURANGI RESIKO PENURUNAN PENDAPATAN BANK SYARIAH INDONESIA KC IMAM BONJOL PADANG - Jeni Vebrianti; Hesi Eka Puteri (BORJUIS: JURNAL OF ECONOMY, 2024)
This research aims to analyze how collateral auctions can resolve problematic financing and their impact on the income risk of banks, focusing on Bank Syariah Indonesia (BSI) Imam Bonjol Padang Branch. The method used is qualitative descriptive with a case study approach, utilizing in-depth interviews, observations, and documentation as data collection techniques. The results show that collateral auctions are an effective mechanism for handling problematic financing. The auction process involves asset valuation, announcement, execution, and the delivery of auction proceeds to the bank. This mechanism helps reduce the risk of income decline for the bank. The success of the auction depends on accurate asset valuation, process transparency, and cooperation between the bank, debtor, and auction institution. In conclusion, collateral auctions are an effective solution for addressing problematic financing and reducing the risk of income decline for banks. The research recommendations include enhancing asset valuation capacity, ensuring transparency in the auction process, and strengthening cooperation among related parties. The study also highlights the importance of finding solutions to challenges in asset valuation and the auction process at BSI Imam Bonjol Padang Branch.